Problems of modelling carbon biogeochemical cycle in agricultural landscapes - O.E. Sukhoveeva (Учёные записки Казанского университета: Серия Естественные науки)
The research is focused on the carbon cycle features in soil that are formed under agricultural land use and should be taken into account for mathematical simulation, including assessments of greenhouse gases emissions and specific carbon balance in arable soils. A classification of carbon models was developed; global (carbon-nitrogen and multi-element) and ecosystem models were singled out. The latter ones fall into carbon cycle models (agroecosystem, phytocenosis, and greenhouse gases (СО2 and СН4) emissions) and carbon-nitrogen cycle models (various ecosystems, forest, and microbiological). The following difficulties arising when mathematical methods are used for description of the carbon cycle were discussed: multiple methods of calculation; high requirements to input data; limited availability of input information; necessity to consider climate change; errors in description of the functional dependence of CO2 emission on temperature. The challenges of quantitative evaluation of components of the carbon biogeochemical cycle were analyzed, i.e., the dual role of soil both as a carbon stock and a source of carbon compounds, which are greenhouse gases, as well as the interaction of carbon and nitrogen cycles, separation of the pool of soil organic carbon into fractions, and the ratio of microbial and root respirations. Further development of the obtained models will help to better assess greenhouse gases fluxes, to properly determine the effect of climatic and anthropogenic factors on them, and to create a strategy for reducing their emissions.